Desorption kinetics of tetracyclines in soils assessed by diffusive gradients in thin films. (January 2020) - Ren, Suyu; Wang, Yi; Cui, Ying; Wang, Yan; Wang, Xiaochun; Chen, Jingwen; Tan, Feng
Abstract: Tetracyclines (TCs) are frequently detected in agricultural soils worldwide, causing a potential threat to crops and human health. In this study, diffusive gradients in thin films technique (DGT) was used to measure the distribution and exchange rates of three TCs (tetracycline (TC), oxytetracycline (OTC) and chlortetracycline (CTC)) between the solid phase and solution in five farmland soils. The relationship between the accumulated masses with time suggested that TCs consumption in soil solution by DGT would induce the supply from the soil solid phase. The distribution coefficient for the labile antibiotics ( K dl ), response time ( T c ) and desorption/adsorption rates ( k b and k f ) between dissolved and sorbed TCs were derived from the dynamic model of DIFS (DGT induced fluxes in soils). The K dl showed similar sizes of labile solid phase pools for TC and OTC while larger pool sizes were observed for CTC in the soils. Although the concentrations of CTC were lowest in soil solution, the potential hazard caused by continuous release from soil particles could not be ignored. The long response time (>30 min in most cases) suggested that the resupply of TCs from soil solids was limited by their desorption rates (1.26-121 × 10 −6 s −1 ). The soils in finer texture, with higher clay and silt contents (<50 μm) showed a greater potential for TCs release. Graphical abstract: Image 1 Highlights: TCs desorption kinetics in agricultural soils were assessed by DGT. Consumption of TCs by DGT would induced resupply of TCs from soil particles. The distribution coefficients, and kinetic parameters were obtained from 2D-DIFS. Soil texture had the most significant impact on the extent of TCs desorption. Abstract : Tetracyclines desorption kinetics in five type agricultural soils were assessed by DGT coupled with the 2D-DIFS model.